Relation between financial indicator and corporate governance to tax avoidance in Indonesia - Muhammad Hasbiy, Suparna Wijaya, (Opción)
This study examined whether a relationship exists between key financial indicator and corporate governance toward tax avoidance in the manufacture industry in Indonesia. Results showed that cash flows from operations and debt dependency were related to tax avoidance. By contrast, noncurrent assets to noncurrent financing ratio exhibits no relationship with tax avoidance. Audit committee and independent commissioner did not show the same results. On these bases, manufacture industry in Indonesia made use of debt to reduce taxable income while still followed the debt to equity ratio. Besides, companies held their operating cash flow in order implemented tax avoidance